Identifikasi Siklamat Pada Kuah Dadar Gulung Yang Dijual Di Kawasan Pelabuhan Rambang Kota Palangka Raya - Nurul Qamariah; Karmila Karmila (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
The purpose of this study was to find out whether the rolled omelet sauce sold in the Rambang Port Area in Palangka Raya City contained artificial sweetener of cyclamate. This research is a type of experimental research by conducting a series of experiments which then obtained data from the results of the laboratory research and analyzed descriptively. The research sample was a rolled omelet sauce sold in the Rambang Port Area in Palangka Raya City. Data collection techniques using saturated sampling is by taking all the population as a sample because the population is relatively small, then the data is made in table form. Sampling was conducted on 19 May 2016 at 14.50 WIB for the first sample, at 15.00 WIB for the second sample and at 15.15 WIB for the third sample. From the identification results of artificial cyclamate sweeteners in roll omelet namely in sample 1, sample 2 and sample 3, after being tested there were no white deposits as happened in the positive control. So it can be concluded that the sample was not detected containing cyclamate.